Socio-Demographic Predictors of Willingness to Pay for Premium of National Health Insurance: A Cross-sectional Survey of Six Districts in Sierra Leone - Peter Agyei-Baffour; Abraham Isiaka Jimmy; Peter Twum; Deborah Larbie; Kwabena Anarfi Boateng; Ibrahim Kwaku Duah; Abdul Bangura; Hassan Milton Conteh (Kerman University of Medical Sciences, 2022)
Background  The government of Sierra Leone introduced Social Health Insurance Scheme as a measure to remove financial barriers that beset the people in accessing health to ensure universal coverage. Under this policy, the citizens were encouraged to subscribe to the scheme to avoid out of pocket payment for healthcare at the point of use. This study was conducted to find out the predictors of willingness among the people to pay for health insurance premium.   Methods  A cross-sectional study design was employed in six selected districts in Sierra Leone. Quantitative data was collected for this study through the use of semi-structured questionnaire with a sample size of 1185 respondents. Data was analysed into descriptive and inferential statistics using the contingent valuation model. Statistical analysis was run at 5% significant level using Stata version 14.0 software.   Results  The results showed that majority of the respondent are willing to join and pay a monthly premium of Le 10 000 (US$1.03) with an estimated mean contribution of about Le 14 089 (US$1.44) and the top five predictors of willingness to pay (WTP) were household monthly income, age, district of resident, gender, and educational qualification.   Conclusion  The findings on predictors of WTP premium of Sierra Leone National Social Health Insurance (SLeNSHI), suggests that the socio-demographic characteristics of the population are important in premium design and payment. Efforts at improving the socio- economic statuses of the population could be helpful in premium design and payment.